Advanced control engineering / Roland S. Burns. - Burns, Roland S. (Butterworth-Heinemann, 2001)
Advanced Control Engineering provides a complete course in control engineering for undergraduates of all technical disciplines. Included are real-life case studies, numerous problems, and accompanying MatLab programs.